2002
DOI: 10.1590/s0100-879x2002001100016
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-wake pattern of medical students: early versus late class starting time

Abstract: The sleep-wake cycle of students is characterized by delayed onset, partial sleep deprivation and poor sleep quality. Like other circadian rhythms, the sleep-wake cycle is influenced by endogenous and environmental factors. The aim of the present study was to determine the effects of different class starting times on the sleep-wake pattern of 27 medical students. The data were collected during two medical school semesters having different class starting times. All subjects answered the Portuguese version of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
44
0
15

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 14 publications
6
44
0
15
Order By: Relevance
“…The results indicated that there was a significant relationship between sleep duration and professional operation as well as mental awareness of people. Moreover, in students, sleep deprivation can affect their academic status (17). Sleep is one of the basic human needs and in Maslow's needs hierarchy, it is placed in line with physiological needs.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that there was a significant relationship between sleep duration and professional operation as well as mental awareness of people. Moreover, in students, sleep deprivation can affect their academic status (17). Sleep is one of the basic human needs and in Maslow's needs hierarchy, it is placed in line with physiological needs.…”
Section: Discussionmentioning
confidence: 99%
“…Dessa forma, considerando que na população dos estudantes de Medicina e residentes observa-se padrão irregular do ciclo sono-vigília e alta prevalência dos transtornos do sono [10][11][12][13][14][15][16][17][18] , além de uma escassez de pesquisas locais sobre o assunto, o presente trabalho se propôs a avaliar os hábitos do sono de estudantes da graduação e residentes da Faculdade de Medicina da Universidade Federal de Goiás (UFG), possibilitando identificar os principais fatores que afetam a qualidade do sono da amostra a ser analisada.…”
Section: Introductionunclassified
“…Not surprisingly, the daily schedule of activities has a major impact on sleep quality. A study of Brazilian medical students (n = 27), positively correlated later class-start times with better sleep quality and longer sleep duration (Lima, Medeiros, and Araujo 2002).…”
Section: Sleepmentioning
confidence: 99%